PENGARUH PENAMBAHAN SARI WORTEL DALAM PENGENCER SITRAT KUNING TELUR TERHADAP KUALITAS SPERMATOZOA KAMBING BLIGON (The effect of carrot juice supplementation in citrate - egg yolk extender on spermatozoa quality of bligon goat) - Maria Epifania Barek; kirenius uly; Thomas Mata Hine; Wilmientje Marlene Nalley; Henderiana L.L. Belli (JURNAL NUKLEUS PETERNAKAN, 2020)
This study aims to determine the effect of adding various doses of carrot juice into citrate-egg yolk diluents (C-EY) on bligon buck semen quality. Semen was collected twice a week using an artificial vaginal method of three buck with normal body condition and reproductive organs. Semen was 70% of motility, konsentration ≥1000x106mL and abnormality ≤ 15 diluted with C-EY added with carrot juice at a concentrations: 0% (CJ-0), 10% (CJ-10), 12.5% (CJ-12,5), 15% (CJ-15), 17.5% (CJ-17,5), and 20% (CJ-20), and stored in a refrigerator at 3-5o C. The quality of spermatozoa was evaluated every 24 hours. The Variables measured were spermatozoa motility, viability, and abnormalities. The results showed that spermatozoa preserved by C-EY supplemented by 17.5% carrot juice (CJ-17.5) had a higher quality (P<0.05) compared to the other four treatments, with motility (49.04 ± 1.0%), viability (55.70 ± 1.22%), dan abnormalities (4.57 ± 0.88 %) on the 4th day of storage. This study concludes that 17.5% carrot juice into citrate eggyolk extender improves the bligon buck semen